Gynaecological disease in the developing world: a silent pandemic. (29th August 2018) - Wijeratne, Dileep; Fiander, Alison
Abstract : Key content: Gynaecological conditions are major contributors to morbidity and mortality worldwide, with the greatest burden of disease borne by women in low‐resource countries (LRCs). Approximately 4.5% of the overall global disease burden can be attributed to gynaecological disease, which exceeds that of other major global health priorities such as malaria (1.04%), tuberculosis (1.9%), ischaemic heart disease (2.2%) and maternal conditions (3.5%). There is a health workforce crisis in most LRCs, leaving few specialists or other healthcare cadres to manage gynaecological conditions. Many LRCs could prevent or treat a broad spectrum of gynaecological disease using cheap and widely available drugs and resources. The Royal College of Obstetricians and Gynaecologists' Essential Gynaecology Skills (EGS) course is a novel teaching programme that provides training in evidence‐based, patient‐centred gynaecological care to improve quality of care and better use the scarce resources that are available in LRCs. Learning objectives: To understand the burden and distribution of key gynaecological conditions that contribute to the large disease burden in LRCs. To understand some of the barriers that prevent gynaecological conditions being treated as global health priorities. Ethical issues: The inequitable burden of gynaecological disease borne by women in LRCs is related to widespread structural barriers, including gender inequality, sociocultural stigma and restrictive laws.